Growth dynamics of orbit and lens in prenatal goat - PARMAR, M L; MALIK, M R; TALUJA, J S (The Indian Journal of Animal Sciences, 2014)
The growth spurt of orbit and lens was studied on 21 goat foetuses in early, mid and late gestation. The growth spurt showed higher total increase (groups 1-3) of width than length of the orbit. The depth of the orbit revealed minimum and maximum increase in groups 1-2 and 2-3 respectively. All the measurements of the orbit showed greater increase In early stage of gestation than late in contrary to lens which revealed higher increase in late gestation. The circumference of lens was 45.66%, 31.82% and 39.49% of the orbital circumference in groups, 1,2 and 3 respectively. The orbital length and depth ratio and lens diameter and thickness ratio were in approximation throughout the gestation.